1999
DOI: 10.1097/00003246-199908000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Prospective, randomized, controlled clinical trial comparing traditional versus reduced tidal volume ventilation in acute respiratory distress syndrome patients

Abstract: The reduced tidal volume strategy used in this study was safe. Failure to observe beneficial effects of small tidal volume ventilation treatment in important clinical outcome variables may have occurred because a) the sample size was too small to discern small treatment effects; b) the differences in tidal volumes and plateau pressures were modest; or c) reduced tidal volume ventilation is not beneficial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
228
1
18

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 496 publications
(256 citation statements)
references
References 31 publications
7
228
1
18
Order By: Relevance
“…As a result of the systematic review, only six 2013 Cochrane Review202‐adopted RCTs191, 203, 204, 205, 206, 207 involving the use of lung protective ventilation methods focusing primarily on low tidal volume in adult ARDS patients were identified. Mortality statistics were reported in all six studies ( n  = 1,305), and while there was a difference in the follow‐up period, this period tended to be shorter in the low tidal volume group (risk ratio: 0.84, 95% confidence interval [CI]: 0.67–1.07).…”
Section: Cq10: Management Of the Mechanically Ventilated Patientmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of the systematic review, only six 2013 Cochrane Review202‐adopted RCTs191, 203, 204, 205, 206, 207 involving the use of lung protective ventilation methods focusing primarily on low tidal volume in adult ARDS patients were identified. Mortality statistics were reported in all six studies ( n  = 1,305), and while there was a difference in the follow‐up period, this period tended to be shorter in the low tidal volume group (risk ratio: 0.84, 95% confidence interval [CI]: 0.67–1.07).…”
Section: Cq10: Management Of the Mechanically Ventilated Patientmentioning
confidence: 99%
“…As a result of the systematic review, four RCTs (1,132 patients)191, 204, 205, 207 were identified. Prolonged VFD (2.5 days on average, 95% CI: 0.5–4.45) was confirmed by setting plateau pressure to ≤30 cmH 2 O for 5–7 days after the initiation of mechanical ventilation.…”
Section: Cq10: Management Of the Mechanically Ventilated Patientmentioning
confidence: 99%
“…Ventilation with low tidal volumes in patients with ARDS/ALI is now the standard of care. 1,2,[23][24][25][26] However, patients with ALI represent a minority of ventilated ICU patients and an even smaller fraction of those ventilated in the operating room. It has been suggested that other patients may also benefit from low tidal volumes.…”
Section: Discussionmentioning
confidence: 99%
“…There is convincing evidence that the use of high tidal volumes (12 mL/kg of predicted body weight) results in increased mortality as compared with the use of low tidal volumes (6 mL/kg of predicted body weight) [30]. Unfortunately, the tidal volumes tested in several randomized trials were normalized by the body weight (actual or ideal) [30][31][32][33][34]. This standardization was introduced, although not explicitly stated, as a surrogate for standardization of the lung size.…”
Section: Assessment Of Lung Protection and Setting The Tidal Volumementioning
confidence: 99%